Experiment on Size Effect and Fractal Characteristics of Waste Brick and Concrete Recycled Aggregate. (16th October 2021) - Li, Hongbo; Zhang, Hubiao; Yan, Pengfei; Tong, Yufei; Yan, Changyu; Ding, Yongfa
Abstract : Herein, the size effect of single-particle crushing of recycled brick and concrete recycled macadam under static load and the fractal characteristics of aggregate under impact load are investigated. The mechanical change law of recycled macadam after compaction crushing under static load is analyzed through single-particle load crushing and impact crushing tests with different particle groups. Furthermore, the fractal dimension D is introduced to study the effects of impact energy, particle size, and different materials on the fractal characteristics of the recycled macadam. Consequently, the material, shape, and particle size of a single-particle significantly affect the crushing strength under static loading, and there is an apparent size effect on the crushing strength. Moreover, the proportion of unbroken particles in the overall mass sieve increased with decreasing particle group order under impact loading. The proportion of unbroken particles in the 4.75–9.5-mm group constituted more than 60% of the total, indicating that its anticrushing ability was significant. In addition, the model relationship between fractal dimension D, nonuniformity coefficient, and curvature coefficient is established. When 1.887 ≤ D ≤ 2.631, the gradation of recycled macadam is superior.